The Dialectic of the Sacred and the Profane in the Religious Tradition of Nyalase Among the Madurese Community - ABD MUNIB (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2025)
This article aims to explore the dialectic or encounter between the sacred and the profane within the nyalase religious tradition of the Madurese community. Nyalase is a customary practice in which members of the community gather at burial grounds to perform rituals such as cleaning the gravesite, planting ornamental plants on the graves, sharing meals at the cemetery, and holding communal prayers and tahlil (Islamic litany). These activities exemplify a dialectical process. The dialectic referred to in this study draws from Hegelian philosophy, in which two seemingly opposing elements are brought into reconciliation. To this day, the nyalase tradition remains actively practiced in Madura. In order to analyze the dialectic between the sacred and the profane within this tradition, the study refers to the thought of Mircea Eliade, who argues that human activity often simultaneously invokes both sacred and profane experiences. The sacred refers to that which holds spiritual or holy significance, while the profane denotes that which is considered ordinary or devoid of spiritual value. This research adopts a literature review method, utilizing books, articles, and other relevant references to explore the object of study. The findings indicate that the nyalase tradition serves as a mediating practice between the sacred and the profane, allowing the local community to encounter the experience of the sublime.